Royal fairy tales for bedtime - Mackinnon, Mairi; Alvarez, Lorena (Usborne Publishing Ltd London, 2012)
A regal collection of much-loved classics and some less familiar tales, perfect for reading aloud and sharing at bedtime. Book includes favourites such as The Frog Prince, The Emperor's New Clothes, Sleeping Beauty and many more. A lovely gift to be shared together time and time again.